The Effectiveness of Pre-Lecture Quiz in Improve Students' Fluency Thinking Skills of Buffer Solution Topic - Citra Rauda Alza; Ratu Betta Rudibyani; Emmawaty Sofya (Jurnal Pendidikan dan Pembelajaran Kimia, 2019)
This research was aimed to describe the effectiveness of the Pre-Lecture Quiz in improving students' ability to fluency thinking skill on buffer solution topics. The method was quasi-experimental with a pretest-posttest non-equivalent control group design. The population of this research was all students of XI science at SMA in Bandar Lampung as many as 8 classes. The sample was taken by cluster random sampling and obtained samples of class XI IPA 2 as an experimental class (variations of learning Pre-Lecture Quiz) and class XI IPA 4 as a control class (learning Non-Pre-Lecture Quiz). The effectiveness of Pre-Lecture Quiz was showed by the significant difference for average n-Gain of fluency thinking skill between the experimental and control class, for the experimental class was 0.71 with “high” categorize and for control class was 0.20 with “low” categorize. It can be concluded that Pre-Lecture Quiz effective and a huge effect on improving student’s fluency thinking skills of buffer solution topics.Keywords: Buffer Solution, Fluency Thinking Skill, Pre-Lecture Quiz.Penelitian ini bertujuan untuk mendeskripsikan efektivitas Pre-Lecture Quiz dalam meningkatkan kemampuan berpikir lancar siswa pada materi larutan penyangga.  Metode penelitian ini menggunakan metode Kuasi eksperimen dengan pretest-posttest non-equivalent control group design.  Populasi penelitian ini berasal dari semua siswa kelas XI IPA SMA di Bandar Lampung sebanyak 8 kelas.  Diperoleh sampel yang secara cluster random sampling dan diperoleh sampel kelas XI IPA 2 sebagai kelas eksperimen (variasi pembelajaran Pre-Lecture Quiz) dan kelas XI IPA 4 sebagai kelas kontrol (pembelajaran Non Pre-Lecture Quiz). Efektivitas Pre-Lecture Quiz ditunjukkan oleh perbedaan rata-rata n-Gain keterampilan berpikir lancar siswa yang signifikan antara kelas eskperimen dan kelas kontrol yaitu kelas eksperimen sebesar 0,71 berkatagori “tinggi” dan kelas kontrol sebesar 0,20 berkatagori “rendah”. Kesimpulan penelitian ini yaitu Pre-Lecture Quiz efektif dan mempunyai ukuran pengaruh yang besar untuk meningkatkan keterampilan berpikir lancar siswa pada materi larutan penyangga. Kata kunci: Larutan Penyangga, Keterampilan Berpikir Lancar, Pre-Lecture Quiz.